Typing of Erwinia Chrysanthemi isolated from josapine pineapple in Malaysia using antimicrobial susceptibility, plasmid profiles, ERIC-PCR and RFLP analysis - Abd Mutalib, Sahilah; Laboh, Rozeita; Md Shah, Umi Kalsum; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Ninety one leaf samples of Josapine pineapple cultivar (Kelantan, n=8; Pahang, n=20; Perak, n=11; Sabah, n=15; Johor, n=37) showing symptoms of heart rot disease were collected to determine the incidence of Erwinia chrysanthemi. Sixteen strains of E. chrysanthemi were isolated from 13 leaf samples from Pahang (n=4), Sabah (n=2) and Johor (n=7). All of the E. chrysanthemi strains displayed resistance to bacitracin with two strains showing resistance to sulfamethoxazole. None of the E. chrysanthemi strains were resistant toward ampicillin, carbenicillin, cephalothin, ceftriaxone, cefuroxime, gentamicin, kanamycin, nalidixic acid, penicillin G, streptomycin and tetracycline. All of the E. chrysanthemi strains were plasmidless. The dendrogram generated from the ERIC-PCR fingerprinting showed that the E. chrysanthemi strains formed 4 clusters and 7 single isolates at 80% similarity level. The restriction fragment length polymorphism (RFLP) analysis for 16 strains of E. chrysanthemi with HinfI and HaeIII endonuclease, 2 and 4 restriction profiles were obtained, respectively. The combinations of the four techniques were able to differentiate the 16 E. chrysanthemi strains into 14 genome types, suggesting a wide diversity of strains examined. ERICPCR fingerprinting method is found to be more discriminating and useful for the determination of the E. chrysanthemi strains relatedness.